Prodigal Brothers - Hoh, I.K (Evans Brothers Ltd, 1967)
Prodigal Brother is a human little play about very human problems. The Reverend Doe has his pastoral role-which is not easy-while Mary, his wife, is much concerned with bringing up their two boys whose behaviour worries her.The boys,themselves, are not without troubles: one is greedy and light-fingered; the other is at the age when he must flirt with every girl he sees. Mr. Tulli and his daughter are victims of this.
Keywords: African(English); Brothers; Drama